The Investigation of the Mechanical Behavior of a Braided Parachute Suspension Line Using a Mesomechanical Finite Element Model - Catherine P. Barry; Keith Bergeron; Scott E. Stapleton; David J. Willis; Gregory Noetscher; Christine Charrette; James A. Sherwood (Textiles, 2025)
Parachute suspension lines shed vortices during descent, and these vortices develop oscillating aerodynamic forces that can induce forced parasitic vibrations of the lines, which can have an adverse impact on the parachute system. Understanding the line’s mechanical behavior can assist in studying the vibrations experienced by the suspension lines. A well-calibrated structural model of the suspension line could be used to help to identify how the braid’s architecture contributes to its mechanical behavior and to explore if and how a suspension line can be designed to mitigate these parasitic vibrations. In the current study, a mesomechanical finite element model of a polyester braided parachute suspension line was constructed. The line geometry was built in the Virtual Textile Morphology Suite (VTMS), and a user material model (UMAT) was implemented in LS-DYNA® release 14 to describe the material behavior of the individual tows. The material properties were initially calibrated using experimental tension tests on individual tows, which exhibited an initial modulus of ~4100 MPa before transitioning to ~3200 MPa at a stress of 30 MPa. When these properties were applied to the full braid model, slight adjustments were made to account for geometric complexities in the braid structure, improving the correlation between the model and experimental tensile tests. The final calibrated model captured the bilinear tensile behavior of the braid, with an initial modulus of 2219 MPa and a secondary modulus of 1350 MPa, compared to experimental values of 2253 MPa and 1420 MPa, respectively, showing 2% and 5% differences. The calibrated model of the braided cord was then subjected to torsion, and the results showed good agreement with dynamic and static experimental torsion tests, with a difference of 8–19% for dynamic tests and 13–27% for static tests when compared to experimental values. The availability of virtual models of suspension lines can ultimately assist in the design of suspension lines that mitigate flow-induced vibration.